2004
DOI: 10.1128/aem.70.2.1207-1212.2004
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Saccharification, and Direct Fermentation to Ethanol, of Amorphous Cellulose by Use of an Engineered Yeast Strain Codisplaying Three Types of Cellulolytic Enzyme

Abstract: A whole-cell biocatalyst with the ability to induce synergistic and sequential cellulose-degradation reaction was constructed through codisplay of three types of cellulolytic enzyme on the cell surface of the yeast Saccharomyces cerevisiae. When a cell surface display system based on ␣-agglutinin was used, Trichoderma reesei endoglucanase II and cellobiohydrolase II and Aspergillus aculeatus ␤-glucosidase 1 were simultaneously codisplayed as individual fusion proteins with the C-terminal-half region of ␣-agglu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
141
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 297 publications
(146 citation statements)
references
References 40 publications
4
141
1
Order By: Relevance
“…However, S. cerevisiae cannot utilize cellulosic materials, and a cellulose saccharification process to produce glucose is necessary before fermentation [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, S. cerevisiae cannot utilize cellulosic materials, and a cellulose saccharification process to produce glucose is necessary before fermentation [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, levels of cellulase expression were deemed low, and did not enable growth and ethanol production using cellulose as the sole carbon source. A later study similarly expressed the three types of cellulases required for cellulose degradation in S. cerevisiae [13]. The EGL and CBH, from Trichoderma reesei, and the BGL, from Aspergillus aculeatus, were co-displayed as -agglutinin fusions on the surface of yeast cells, enabling the liberation of glucose from phosphoric acid swollen cellulose (PASC), and fermentation to ethanol when the cells were pre-grown in rich media.…”
Section: Recombinant Cellulase Expression In Saccharomyces Cerevisiaementioning
confidence: 99%
“…Cho et al [35] showed that, for SSF experiments with a strain producing both a b-glucosidase and enzymes with exo-and endocellulase activity, loadings of externally added cellulase could be reduced. Fujita et al [36,37] reported co-expression and surface display of cellulases in S. cerevisiae. High-cell-density suspensions of a recombinant strain displaying the Trichoderma reesei endoglucanase II, cellobiohydrolase II and the Aspergillus aculeatus b-glucosidase were able to directly convert 10 g l 21 phosphoric acid swollen cellulose (PASC) to approximately 3 g l 21 ethanol.…”
Section: Engineering Cellulolytic Ability Into Eukaryotic Process Orgmentioning
confidence: 99%